Indonesia's New Criminal Code and Its Implication of International Treaties of Human Rights Commitment in Indonesia - Yulio Iqbal Cahyo Arsetyo (JURNAL PENELITIAN SERAMBI HUKUM, 2023)
On the 6th of December 2022, the Indonesian Parliament officially signed the new Indonesian Criminal Code. Although it was signed, the problem is the new Indonesian Criminal Code is still widely rejected by some people in Indonesia one of the reasons is the new Criminal Code decreases democracy and human rights in Indonesia. Indonesia like any other nation had signed several international treaties that focused on human rights, democracy and transparency. The question is the new Indonesian New Criminal code breach Indonesia's commitment to the treaties that protect the human right that it signed? The methodology of this research uses a literature review with the object of an international treaty and uses data and information from internet network tracing which is then expert opinion. The result of the research shows that the new Indonesian criminal code had a potential breach of international commitment to human rights, especially in the freedom of speech and private life because Indonesia lawmakers argue that not all values of human rights will be suitable in Indonesia which is criticized by The United Nation because it's against the universal value of human rights which already ruled in core human rights convention, it can be said that Indonesia had partially breached its international commitment to fully implement the core convention of human rights. This paper will conclude that it’s a big achievement for Indonesia because finally had the original Criminal Code made by the Indonesian but the problem with the new Criminal Code is that Indonesia did not fully integrate with the International Core Convention of Human Rights because of view that not every human right can be implemented in Indonesia although the value of human rights should universal.